2018
DOI: 10.1634/theoncologist.2018-0133
|View full text |Cite
|
Sign up to set email alerts
|

Patient Navigation to Enhance Access to Care for Underserved Patients with a Suspicion or Diagnosis of Cancer

Abstract: Background Interventions aimed at improving access to timely cancer care for patients in low‐ and middle‐income countries (LMIC) are urgently needed. We aimed to evaluate a patient navigation (PN) program to reduce referral time to cancer centers for underserved patients with a suspicion or diagnosis of cancer at a public general hospital in Mexico City. Materials and Methods From January 2016 to March 2017, consecutive patients aged >18 years with a suspicion or diagnosis of cancer seen at Ajusco Medio Genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 14 publications
1
30
0
3
Order By: Relevance
“…Yet, few studies have focused on the role that patient navigation might play in cancer care in LMICs or on how these services can affect health outcomes in countries with fragmented or fragile health systems. In the 14 studies included in the review, the types of patient navigation services that were offered mirrored those provided in HICs, notably facilitating linkages to follow-up services [6, 3135], providing counselling [6, 33, 34, 3639], providing financial support [40], coordinating appointments [32, 33, 35, 39–43], and maintaining communication with patients and families [40, 41, 43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, few studies have focused on the role that patient navigation might play in cancer care in LMICs or on how these services can affect health outcomes in countries with fragmented or fragile health systems. In the 14 studies included in the review, the types of patient navigation services that were offered mirrored those provided in HICs, notably facilitating linkages to follow-up services [6, 3135], providing counselling [6, 33, 34, 3639], providing financial support [40], coordinating appointments [32, 33, 35, 39–43], and maintaining communication with patients and families [40, 41, 43].…”
Section: Discussionmentioning
confidence: 99%
“…While over half of the papers reported on all three types of outcomes (clinical, process and implementation), none of the outcomes demonstrated whether the patient navigation intervention increased the likelihood of survival or improved long-term health outcomes for the patient. For example, articles consistently reported on outcomes such as rates of follow up [6, 31, 33, 38–43], reach or uptake of the patient navigation intervention [6, 31, 38, 4042], and treatment adherence and/or retention [37, 38, 40] and screening rates [38, 40, 41]. This has been a research challenge in HICs as well; data is limited regarding the impact of patient navigation interventions on cancer-specific survival [47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…18 30 60 88 These publications were from the UK, 60 Australia 30 88 and Mexico. 18 A fifth publication only used the patients' area of residence as part of their model. 95 All of the publications were on multiple cancer types and adult populations, although one included a paediatric population.…”
Section: Specific Considerations For Underserved Populationsmentioning
confidence: 99%
“…Many studies in various countries have reported the efficacy of a patient navigation system to overcome the transportation barrier [30][31][32]. The patient navigator assessed many factors that can impact on patient care such as financial burden, medical insurance, fear, and disability through a psychosocial interview, arranged for the appropriate mode of transportation, and monitoring the patient to ensure that they received the appropriated medical care.…”
Section: Special Consideration For Older Cancer Patientsmentioning
confidence: 99%